Go, team. go! - Redbank, Tennant; Batson, Alan; Belisle, Nicole; Eastman, P. D (Philip D.); Netflix (Firm) (New York Random House, 2021)
Tag and Scooch are a team. Will they win race day? It's Race Day, and Tag and Scooch soon learn the most important part about being on a team is teamwork. Based on the P.D. Eastman bestselling classic, Go, Dog. Go! the new Netflix animated series is all about community, friendship, and family
"Based on the book Go, dog, go! by P.D. Eastman © P.A. Eastman Revocable Trust and Alan Eastman LLC"--Title page verso
"Netflix - a Netflix original series"--Cover
English Stories
Ages 4-6
Keywords: Dogs -- Juvenile fiction; Picture books for children; Racing -- Juvenile fiction; Readers (Elementary); Teamwork (Sports) -- Juvenile fiction; Dogs -- Fiction; Racing -- Fiction; Teamwork (Sports) -- Fiction; Dogs; Picture books for children; Racing; Readers (Elementary); Teamwork (Sports); Readers; Animal fiction; Animal fiction; Fiction; Juvenile works; Picture books; Picture books; Readers (Publications); Readers (Publications); Readers